Performance of sodium cooled traveling wave reactor core with axial fuel shuffling strategy - Meiyin Zheng; Ping Chen; Dalin Zhang; Wenxi Tian; Guanghui Su (International Journal of Advanced Nuclear Reactor Design and Technology)
A prototype sodium cooled traveling wave reactor core with axial fuel shuffling, consist of an ignition and breeding region, was designed in this paper. Neutronic and depletion calculation was performed by MCORE with data library of ENDF/B-VII. A self-developed code SAST was used to perform steady state thermal-hydraulic behavior analysis. The results show that the fluctuation of the reactivity and power peak factor is too big, thus the ignition process should be optimized. The initial nuclide density distribution was adjusted and the axial fuel shuffling option was used to optimize the core ignition process. Results show that the maximum reactivity and radial power peak factor fluctuation are reduced to 1.04 % and 11.76 %; the power density distribution and neutron flux distribution move in the opposite direction of the fuel shuffling; power density, neutron flux and nuclide density are shaped like crescents in the core radial direction during equilibrium cycle; the discharged burn-up of the core is non-uniform, the maximum and minimum discharged burn-up of the outer and inner core are 17.7 % and 70.3 %, respectively. The core flow distribution analysis was based on the end of equilibrium cycle (EOEC) power distribution. Results show that maximum and minimum relative power flow ratio during the whole core life are 1.11 and 0.88; maximum fuel and cladding temperature are 676.9 °Cand 560.0 °C during the whole core life, which have a large safety margin to the design values.